Serum antioxidant status in Iraqi women with endometrial cancer - Al- Ruba,ei, Salwa H. N.; Jasim, Rana K.; Al-Rawaq, Khudhair J. S. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Endometrial cancer is the most common gynecologic malignancy in the United States and the fourth most common cancer in women, comprising 6% of female cancers.Objectives: The aim of this study is to investigate the antioxidant vitamins, Coenzyme Q10 and oxidative stress in patients with endometrial cancer.Patients and methods: Fifty six endometrial cancer women patients with various clinical stages (stage 1A, stage1B, stage II, stage III, stage IV) mean aged 58.055 ± 10.561 years, and 30 healthy women volunteers mean aged 39.731 ± 13.504 years, were includes as control group.Results: The results in this study revealed a highly significant decreased (P